Indeks Kepuasan Masyarakat Pelayanan Akta Kelahiran Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Tulungagung - Dewi Bulan Azizah; Hardi Warsono; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
In this era of globalization and reform, the demands of society and the business community to improve the quality of service is getting stronger. The provision of public services to the community at this time it is still a weakness. It is characterized by the presence of a variety of complaints from the public. Given that the primary function of government is to serve the public, then the government needs to improve the quality of service. In improving the quality of care Population Administration in the Department of Population and Civil Registration vBulletin necessary to measure public satisfaction index. Because it makes the authors analyze the quality of care by referring Kemenpan 25 of 2004 on Guidelines for arranging General Public Satisfaction Index and the suitability of the analysis of performance levels and interests through Cartesian diagram.Based on results of this study is that the value of the overall index value of 3.096 and a value of 77.4 IKM so in general it can be seen that the quality of service in the department population and civil registration is GOOD. From 14 elements of the service there are several elements that go very well in the category that is, elements of service personnel discipline (3.35 element value, suitability 97.29%), ministry of justice element (element value of 3.55, the suitability of 107%) and the elements of the charge services (element value of 3.26, the suitability of 100%). However, there are three elements that were considered less important when considered by the community that is the element of service procedures (3,1 element value, suitability 87.24%), speed of service elements (element values 2.69, 78.56% suitability) and elements of courtesy and hospitality workers (element value of 2.97, the suitability of 87.11%) so it should be a priority in order to achieve improved community satisfaction.